Implementasi Program Sosial dan Pendidikan Muhammadiyah: Tinjauan Teoritis Berdasarkan Ali Farazmand - Nugraha, Imam; Rikki Maulana Yusup; Adimiharja, Rochman; Farid, Diana (Pusat Riset dan Inovasi Nasional, 2025)
This paper explores the role of Muhammadiyah ideology in the implementation of public administration, especially in facing the challenges of a complex and slow bureaucracy. As one of the largest religious organizations in Indonesia, Muhammadiyah has the potential to encourage social reform based on Islamic values. This research uses a qualitative approach with literature analysis and case studies to evaluate the implementation of public policies involving Muhammadiyah. The findings show that Muhammadiyah faces obstacles such as public policy dynamics, limited resources, and complexity of administrative procedures. However, bureaucratic reform efforts through simplifying procedures, utilizing information technology, strengthening human resource capacity, and collaborating with various parties provide opportunities for significant improvement. Such strategies not only increase the efficiency of public services but also strengthen Muhammadiyah's role in supporting administrative reform in Indonesia. Muhammadiyah can contribute significantly to public administration by adopting innovative and responsive approaches to changing times, making Islamic values the foundation for sustainable reform.